Patient’s Complaint Jigsaw Card to Teach Speaking Skill For Second Semester Nursing Students - Maharani, Irka; Supriyono, Supriyono; Fauzi, Adin; Sutanti, Nita (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
English is one of subject taught for diploma 3 of nursing students. The problem is low speaking skill and students need improvement on the media to learn patient’s complaint. The researcher combined Jigsaw method and card in teaching Patient’s Complaint, called Patient’s Complaint Jigsaw Card (PCJC). The research objective was to develop PCJC to Teach Speaking Skill for Second Semester Nursing Students. The researcher used simple random sampling. The subject of the research was the students of State Health Polytechnic of Malang (Blitar Campus) they were 25 students and 5 lectures. The technique of analyzing data used qualitative and quantitative. The qualitative data were taken from observation, interview, and documentations. The quantitative data were taken from online pre test, post test, speaking skill evaluation and behavior assessment. From the result of experimental trial, the product could improve students’ speaking ability. There were increase between pre test and post test. P value of T-test was 0.001 which < 0,05. The result of students’ and teachers’ perception toward the use of developed product was strongly agree (students 91% teacher 86%). The result of behavior evaluation, students strongly agree (87%) that by playing PCJC it can change their behavior in their speaking skill.